Results of quality rights on human rights engagement, stigma and attitudes towards mental health among Colombian medical students - Felipe Agudelo-Hernández; Helena Vélez-Botero; Marcela Guapacha-Montoya (PLoS ONE, 2025)
Background Training healthcare professionals in human rights approaches is fundamental for humanizing medical practice and promoting patient autonomy. Aims To evaluate the impact of Quality Rights strategy training on human rights engagement, stigma reduction and attitudes towards mental health among medical students in Colombian. Method A pre-experimental study with pre-post measures was conducted, involving 194 medical students, during the first semester of 2024 in Manizales, Caldas, Colombia. To assess notions and commitment to human rights were used the Human Rights Exposure in Social Work and Human Rights Engagement in Social Work. Attitudes toward people with mental disorders were measured using the Community Attitudes Towards the Mentally III (CAMI) scale, and attitudes toward mental health education were assessed using the Mental Illness Clinicians’ Attitude Scale (MICA). The intervention was based on QualityRights, an initiative of the World Health Organization, which aims to improve the quality of care in mental health services and to promote the human rights of people with psychosocial disabilities. Initial data comparisons were made using the Mann-Whitney U test and the Kruskal-Wallis test. Pretest and postest data were compared using the Wilcoxon test. Results Statistically significant improvements were observed in human rights understanding, reduced stigmatizing attitudes toward mental health and decreased authoritarianism. While students demonstrated enhanced human rights knowledge and less stigmatizing attitudes, we observed a concurrent decrease in benevolence scores. Conclusion The Quality Rights training strategy shows promise in improving medical students’ understanding of mental health conditions and promoting empathetic practices. However, ongoing sustained and monitoring strategies are necessary to ensure long-term adoption of human rights-based attitudes and practices in healthcare settings.